Polyhydroxylated bicyclic isoureas and guanidines are potent glucocerebrosidase inhibitors and nanomolar enzyme activity enhancers in Gaucher cells. - Trapero, A; Alfonso, I; Butters, T; Llebaria, A (2011)
Four diastereomeric series of N-alkylated [6+5] bicyclic isoureas having hydroxyl substituents mimicking glucose hydroxyl groups have been synthesized as potential β-glucocerebrosidase (GCase) inhibitors with the aim of developing pharmacological chaperones for enzyme deficiency in Gaucher disease (GD). The bicyclic compounds differ either by the configuration of the ring fusion carbon atoms or by the nature of the N-alkyl substituents. When assayed for effects on GCase activity, the isoureas displayed selective inhibition of GCase with low micromolar to nanomolar IC(50)'s in isolated enzyme experiments. One of the series of isoureas, a family having a specific cis ring fusion, exhibited strong inhibition of recombinant GCase activity with K(i) values in the 2-42 nM range. In addition, the [6+5] bicyclic guanidine derivatives with a substitution pattern analogous to the most active isoureas were also found to be potent inhibitors of GCase with K(i) values between 3 and 10 nM. Interestingly, the active bicyclic isoureas and guanidines also behaved as GCase inhibitors in wild-type human fibroblasts at nanomolar concentrations. The potential of these compounds as pharmaceutical chaperones was determined by analyzing their capacity for increasing GCase activity in GD lymphoblasts derived from N370S and L444P variants, two of the most prevalent Gaucher mutations. Six compounds were selected from the different bicyclic isoureas and guanidines obtained that increased GCase activity by 40-110% in N370S and 10-50% in L444P cells at low micromolar to nanomolar concentrations following a 3 day incubation. These results describe a promising series of potent GCase ligands having the cellular properties required for pharmacological chaperones.